Psychological and academic stress and its relationship with the level of mental health of high school students: A field study on a sample of high school students - Khemmad, Mohamed; Bennouioua, Said (Journal of Human Sciences, 2023)
The study aimed to find out the relationship between psychological and school pressures experienced by secondary school students and their level of mental health.To achieve the aim of the study, the researcher used the descriptive approach to suit the nature of the study. The study was conducted on a sample consisting of (378) students from secondary schools in Ain al-Hajjal in the state of M'sila. The study reached the following results:- The level of psychological stress and school pressure and the level of mental health among the study sample members all reached the intermediate level.- There is an inverse negative correlation statistically significant between degrees of psychological stress and mental health of secondary school students.- There is an inverse negative correlation statistically significant between degrees of school stress and mental health among secondary school students.